a study of CSR engagement of SOEs in China AUTHOR - QI, YUANZHI (2016)
With the global development of economy, People have gradually realize that the significance of natural resources, ecological environment, employees’ rights and business ethic. In China, managers begin to seek sustainable and harmonious development with environment and employees rather than purely profit oriented especially after China joining WTO. In the background of socialist market economy with Chinese characteristics, stated-owned enterprise as a specific economic entity is a tool for government to intervene and participate in the economy, which has important responsibility to fulfil social responsibility. Thus, it is worth to study corporate social responsibility (CSR) in Chinese enterprise especially for Stated-owned enterprises. Under this background, this paper aim to deep analysis the CSR problems in state-owned enterprises, mainly focus on the CSR engagement. This study chooses Juhua Group Corporation as a case to analysis by using qualitative research method. This study divided into 4 parts including literature review, methodology, finding and analysis as well as discussion and conclusion. Some limitation and recommendations also will be pointed out. According to the analysis of Juhua Group Corporation, SOEs in China have made continuous improvement on fulfilling social responsibility recently, but there still have room to improve such as environmental problems and supervision mechanisms. Some recommendations also have been come up from three dimensions including governmental management, enterprise and social supervision.